Pengaruh Intensitas Aset Tetap, Dewan Komisaris Independen dan Ukuran Perusahaan terhadap Manajemen Pajak dengan Tingkat Utang sebagai Variabel Pemoderasi (Studi Empiris pada Perusahaan Konsumsi Non-Siklikal yang Terdaftar di BEI Periode 2017–2023) - Suryajati, Padmellia; Irawati, Wiwit (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This study aims to examine the effect of fixed asset intensity, independent board of commissioners, and firm size on tax management with debt level as a moderating variable. The sample consists of 25 non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for the 2017–2023 period, resulting in 175 observations. The analysis method used was panel data regression with EViews 10. The results indicate that the independent variables simultaneously affect tax management. Partially, fixed asset intensity and independent commissioners have no effect on tax management, while firm size has a significant negative effect. Debt level does not moderate the relationship between independent variables and tax management.